(untitled) (Bangladesh Heart Journal, 2024)
Introduction Diabetes Mellitus (DM) is one of the important co-morbidity that may negatively influence the clinical outcome of the coronavirus disease 2019 (COVID-19) if it co-exists. There is a paucity of data regarding the characteristics and outcomes of COVID-19 diabetic patients in comparison to non-diabetic patients. Thus, we aimed to compare demographics and clinical characteristics, and in-hospital outcome in COVID-19 positive patients with or without DM. Method This prospective observational study included all consecutive confirmed symptomatic and asymptomatic COVID-19 positive patients from March 8th 2020 to July 7th 2023at the National Heart Foundation Hospital & Research Institute of Bangladesh. Patients were divided into two groups based on whether they had diabetes: Group I- patients with DM and group II- patients without DM. Baseline and clinical characteristics & in-hospital outcome of patients in both groups were assessed for comparison. Result This study included a total of 2506 confirmed COVID-19 positive patients. Of them 1003 (40%) patients had DM (Group-I) & 1503 (60%) were without DM (Group-II). Diabetic COVID-19 positive patients were older (56.87 ±11.84 years vs 45.92 ± 16.91 years; p=0.001) and had more co-morbidities (p= 0.001) than patients without DM. Only 4.2% healthcare personnel had DM. Diabetic patients (G-I) had more risk factors and comorbidities than non-diabetic patients (G-II): cardiovascular disease (90.4% vs 65.7%; p=0.001); hypertension (84.3% vs 41.4%; p=0.001); chronic kidney disease (47.7% vs 29.8%;p=0.001); smoking (37.8% vs 25.9%; p=0.001); dyslipidemia (37.2% vs 17.4%;p=0.001); and chronic obstructive pulmonary disease/bronchial asthma (7.5% vs 4.3%; p=0.001). Most of the patients with DM (G-I) were symptomatic (77.5% vs 66.7%; p=0.001). Shortness of breath was significantly higher in diabetic patients (44.8% vs 30.6%; p=0.001). Sore throat (12.0% vs 2.9%; p=0.001), diarrhea (5.4% vs 1.2%; 0.001), anosmia (10.6% vs 3.8%; p=0.001), and headache (16.5% vs 8.8%; p=0.001) were significantly higher in Group-II patients. Diabetic patients had more severe form of COVID-19 disease (moderate: 3.5% vs 1.4%; p=0.001), (severe: 9.5% vs 4.1%; p=0.001), and (critical ill: 1.3% vs 0.4%; p=0.01).Most of the diabetic patients were hospitalized (52.0% vs 29.6%; p=0.001) and most of the non-diabetic patients were treated either in home isolation or in institutional isolation (70.4% vs 48.0%; p=0.001). COVID-19 patients with DM had worse outcome than patients without DM (mortality rate- 6.1% vs 2.6%; p=0.001). Conclusion COVID-19 diabetic patients were usually older, have more comorbidities, a higher probability of hospitalization, increased risk of severe/critical COVID-19 and associated with higher mortality rate as compared with patients without DM. Bangladesh Heart Journal 2024; 39(2): 108-116